Hydroxychloroquine-induced cardiomyopathy and heart failure in twins - Zhao, Hang; Wald, Joyce; Palmer, Michael; Han, Yuchi (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Hydroxychloroquine (HCQ)-induced cardiomyopathy is one of the rare but severe complications following prolonged HCQ use. However, the exact mechanism of HCQ cardiotoxicity remains unclear and it is difficult to identify risk factors. We present a case of twin sisters who both suffered from systemic lupus erythematosus (SLE) and HCQ-induced cardiomyopathy presenting with decompensated heart failure (HF), suggesting that genetic predisposition might be a factor in HCQ-induced cardiomyopathy.